Determining the Factors That Influence Stunting during Pandemic in Rural Indonesia: A Mixed Method - Esti Yunitasari; Bih O. Lee; Ilya Krisnana; Rayi Lugina; Fitriana Kurniasari Solikhah; Ronal Surya Aditya (MDPI AG, 2022)
Objective: Pandemic causes an increase in the poverty rate. The consequences will be many, including the birth of stunting babies. The COVID-19 pandemic has had an impact on stunting. Analyzing the factors that cause stunting during a pandemic will provide suggestions for effective stunting prevention strategies at the national, regional, community, and household levels. This study aims to determine the factors that influence stunting during the pandemic. Method: We use mixed methods. The respondents of this study were 152 mothers of the Maternal and Child Nutrition Security project, and the sampling technique is Cluster Sampling. Quantitatively using a baseline survey whose analysis uses multiple logistic regression to determine the unadjusted and adjusted odds ratio. The qualitative data used focus group discussions which were analyzed using Nvivo 12 with a questionnaire, and anthropometric measurements of children from surveyed households. Results: This study summarizes the multivariate analysis of stunting determinants in the pandemic era, revealing statistically significant interactions between household sanitation facilities and household water treatment. Significant risk factors for severe stunting during the pandemic were male gender, older child age, coming from a low socioeconomic quintile, not participating in prenatal care at a health facility, and mother's involvement in choices about what to prepare for Community House. The FGDs identified misinformation about childcare and consumption of sweetened condensed milk as significant contributors to child malnutrition. Conclusions: Lack of sanitation facilities and untreated water are contributing factors. Water, sanitation, and hygiene initiatives must be included into Indonesian policies and programs to combat child stunting during a pandemic. The need for further research related to government assistance for improving toddler nutrition, as well as the relationship between WASH and linear development in early infancy should be explored.